« Par les sentiers de la montagne enneigée… » Perspectives historiques sur les parcours migratoires à travers la frontière franco-italienne (1945-1960) - Philippe Hanus (Revue de Géographie Alpine)
The goal of this article is to examine the processes that (both legal and illegal) migration flows across the French-Italian Alps entailed between 1945 and 1960, a period that covers the last big wave of Italian emigration to France. Beyond the analysis of public policies aimed at selecting and managing “desirable migrants”, the study of individual journeys made through a cross-border micro-area – that is, the Aosta and Suse valleys, Beaufortain, Briançonnais and Maurienne – enriches our understanding of mobility phenomena. Special care is taken to show, through eyewitness accounts, the experiences of people involved in the migration.